Correlation between Chest Computed Tomography Severity Scores and Age of Adult Patients with Suspected Covid-19 Pneumonia Admitted in Intensive Care Unit of a Tertiary Care Hospital, Bangladesh - Biswas, Ananta Kumar; Hossain, Shahadat; Sarkar, Tapas Kumar; Hossain, Mohammad Ahad; Ahmed, Sabbir; Sanjowal, Lipika (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
In Bangladesh, the second wave of Covid-19 was devastating. Mostly RT-PCR is used to determine the Covid-19 infection. But when test results are delayed, or when there is a clinical suspicion of Covid-19 despite initial negative RT-PCR testing, CT scan of chest was used to detect Covid-19 and Covid-19 severity. This observational cross-sectional study was carried out at Corona dedicated ICU of Bangabandhu Sheikh Mujib Medical College Hospital, Faridpur during February to June, 2021 to observe the HRCT severity score of the patient and its correlation with different ages. A total of 50 patients with clinically suspected Covid-19 cases who were admitted to the Corona dedicated ICU were included in the study. The chest HRCT images of study participants was gathered, CT severity score was calculated by a particular assignment radiologist. Based on this score; Severe disease was mainly seen in the >60 year age group (50%). A significant moderate positive correlation was observed between age and CT chest severity score. With the increasing age the patients were suffering more and being male may increase the risk and put the patient to get admitted in the ICU, and as an alternative of the RT-PCR, CT scan of chest could be useful. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(2):77-82